2020
DOI: 10.3390/nu12020323
|View full text |Cite
|
Sign up to set email alerts
|

Pomace Olive Oil Concentrated in Triterpenic Acids Restores Vascular Function, Glucose Tolerance and Obesity Progression in Mice

Abstract: Pomace olive oil, an olive oil sub-product, is a promising source of bioactive triterpenoids such as oleanolic acid and maslinic acid. Considering the vascular actions of pomace olive oil and the potential effects of the isolated oleanolic acid on metabolic complications of obesity, this study investigates for the first time the dietary intervention with a pomace olive oil with high concentrations of the triterpenic acids (POCTA), oleanolic and maslinic acid, during diet-induced obesity in mice. The results de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 45 publications
3
29
0
Order By: Relevance
“…Our results indicated that only the animals fed the diet enriched with saturated fat (butter) showed significantly higher values of body weight and adiposity (total visceral fat) compared to control and EVOO diets, although the EVOO diet contained the same energy density, and that no marked differences were recorded in food intake although a significant reduction in food intake was established in the butter diet at the end of the experimental period, probably as a response to the increase in body weight. This beneficial effect of olive oil in the regulation of body weight has been described in previous works [ 19 , 20 , 21 , 22 ] and could be related to the minor components included in the unsaponifiable fraction of EVOO [ 23 ] and gut dysbiosis [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 68%
“…Our results indicated that only the animals fed the diet enriched with saturated fat (butter) showed significantly higher values of body weight and adiposity (total visceral fat) compared to control and EVOO diets, although the EVOO diet contained the same energy density, and that no marked differences were recorded in food intake although a significant reduction in food intake was established in the butter diet at the end of the experimental period, probably as a response to the increase in body weight. This beneficial effect of olive oil in the regulation of body weight has been described in previous works [ 19 , 20 , 21 , 22 ] and could be related to the minor components included in the unsaponifiable fraction of EVOO [ 23 ] and gut dysbiosis [ 24 , 25 ].…”
Section: Discussionsupporting
confidence: 68%
“…Additionally, numerous studies have shown that polyphenols such as resveratrol, curcumin or gingerenone A were able to inhibit adipogenesis and AT mass in rodent models [ 24 , 50 ]. Indeed, olive oil extracts rich in oleuropein, hydroxytyrosol and triterpenic acids present protective effects against adipose tissue damage and obesity-associated metabolic disorders in HF diet rodent models [ 51 , 52 ]. Of note, the latter studies were interested in WAT from various origins (epididymal, mesenteric, retroperitoneal, perirenal and inguinal AT) but not peripancreatic WAT.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Djeziri et al [ 151 ] have pointed out that supplementation of drinking water with OA (50 µg/mL) for 16 weeks to HFD-induced obese C57BL/6J female mice, caused a signification reduction in glycemia after an IPGTT test. More recently, Claro-Cala et al [ 152 ] administered a pomace olive oil rich in triterpenic compounds, including OA, to obese mice for 20 weeks and reported a significant improvement in oral glucose tolerance and intraperitoneal insulin sensitivity compared to obese control mice. The intake of the triterpenoid-rich oil improved both the oral glucose (GTT) and insulin tolerance tests (ITT).…”
Section: Biological Activity Of Oamentioning
confidence: 99%
“…In agreement with these results, a significant reduction in the gene expression of IL-1β and IL-6 in the liver and adipose tissue, as well as of TNFα in adipose tissue of HFD-induced obese C57BL/6J female mice was observed by Djeziri et al [ 151 ]. Obese mice fed a high-fructose diet presented increased RNA expression of TNFα and MCP-1 in white adipose tissue and liver, which was ameliorated after being fed pomace olive oil rich in tritepenes, including OA [ 96 , 152 , 161 ]. In addition, Gamede et al [ 153 ] found decreased plasma proinflammatory cytokines, including TNF-α and IL-1β in Sprague Dawley rats fed a high fat, high carbohydrate diet after a 20-week treatment with OA.…”
Section: Biological Activity Of Oamentioning
confidence: 99%